2020
DOI: 10.1080/20008198.2020.1767986
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the cerebellum in EMDR efficiency: a metabolic connectivity PET study in PTSD

Abstract: Background: We recently reported an improvement of precuneus PET metabolism after EMDR therapy in military participants suffering from PTSD. Objective: The aim of the present study was to investigate the metabolic changes of precuneus connectivity in these participants after such treatment. Method: Fifteen participants with PTSD performed a brain 18F-FDG-PET sensitized by virtual reality exposure to war scenes, before and after EMDR treatment. Interregional correlation analysis was performed to study metabolic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 43 publications
1
3
0
Order By: Relevance
“…Alterations in the SN were also reported, with another study considering the cerebellar lobules V-VI together with the posterior insula and the precuneus as part of the posterior Salience Network (SN) and reporting that individuals with PTSD showed increased connectivity between the latter and the posterior insula, the cuneus and precuneus, while they exhibited decreased connectivity between the posterior SN and the dlPFC and the supramarginal gyrus ( Nicholson et al, 2020 ). This is in line with a recent study which showed that decreased connectivity between cerebellar lobule VI and Crus I with the precuneus was associated with a decrease in clinical symptoms in a PTSD sample, after a trauma-focused intervention ( Verger et al, 2020 ) and another study that showed that ALFF in the precuneus and the cerebellar Crus I, among other regions, predicted whether PTSD patients would be responsive to paroxetine treatment ( Yuan et al, 2018 ) Also, decreased FC was reported between the cerebellum and the dorsal anterior cingulate cortex (dACC), another major player of the SN( Seeley et al, 2007 ), in trauma-exposed individuals with and without PTSD versus healthy controls ( Chen et al, 2019 ).…”
Section: Discussionsupporting
confidence: 93%
“…Alterations in the SN were also reported, with another study considering the cerebellar lobules V-VI together with the posterior insula and the precuneus as part of the posterior Salience Network (SN) and reporting that individuals with PTSD showed increased connectivity between the latter and the posterior insula, the cuneus and precuneus, while they exhibited decreased connectivity between the posterior SN and the dlPFC and the supramarginal gyrus ( Nicholson et al, 2020 ). This is in line with a recent study which showed that decreased connectivity between cerebellar lobule VI and Crus I with the precuneus was associated with a decrease in clinical symptoms in a PTSD sample, after a trauma-focused intervention ( Verger et al, 2020 ) and another study that showed that ALFF in the precuneus and the cerebellar Crus I, among other regions, predicted whether PTSD patients would be responsive to paroxetine treatment ( Yuan et al, 2018 ) Also, decreased FC was reported between the cerebellum and the dorsal anterior cingulate cortex (dACC), another major player of the SN( Seeley et al, 2007 ), in trauma-exposed individuals with and without PTSD versus healthy controls ( Chen et al, 2019 ).…”
Section: Discussionsupporting
confidence: 93%
“…Previous functional connectivity studies have confirmed that there are strong links between the posterior cerebellum and the temporal lobes, suggesting these regions share neural similarities and are involved in sensory integration and emotional processing (Yeo et al, 2011;Chan et al, 2019;Heleven et al, 2019;Van Overwalle et al, 2020b). In addition, several positron emission tomography (PET) studies suggest that the posterior cerebellum is involved in various emotional responses, such as fear, sadness, and happiness (Schwartz and Davidson, 1997;Turner et al, 2007;Verger et al, 2020) S2, S3, and Table 2). These results indicate that DFNs are reproducible during repeated movie viewing, further demonstrating that the naturalistic paradigm provides reliable experimental conditions for measuring DFNs.…”
Section: Discussionmentioning
confidence: 94%
“…In addition to autonomic measures, a number of articles cite positron emission tomography data on improvement of cerebellar and precuneus metabolism (following therapy) [ 32 , 33 ], as well as of cardiovascular function [ 59 ].…”
Section: Psychophysiological Methods Of Vret Effectiveness Assessmentmentioning
confidence: 99%
“…Verger [ 32 ] conducted a study where therapy based on eye movement desensitization and reprocessing (EMDR) was combined with stress exposure to VR war scenes and reported a positive sign evidenced by improvement in precuneus metabolism (according to positron emission tomography) in servicemen with PTSD. After EMDR, connectivity reduction of metabolic changes between the precuneus and large bilateral clusters of cerebellum posterior areas (cerebellar lobules Crus I and VI) was observed concurrently with reduction of PTSD clinical manifestations severity.…”
Section: Mechanisms Of Vret Therapeutic Effectmentioning
confidence: 99%